Brain target occupancy of LY3372689, an inhibitor of the O‐GlcNAcase (OGA) enzyme: Translation from rat to human - Shcherbinin, Sergey; Kielbasa, William; Dubois, Susan; Lowe, Stephen L; Phipps, Krista M; Tseng, James; Kevin, Donnelly B; Natanegara, Fanni; Warner, Susan; Dreyfus, Nicolas; Lindsay‐Scott, Peter; Hawk, Mai Khanh; et al. (Alzheimer's & dementia, 2020)
Background LY3372689, an O‐GlcNAcase (OGA) enzyme inhibitor, is being developed as a potential treatment of tauopathies, including Alzheimer’s disease. OGA inhibition is proposed to delay the progression of tau‐related diseases by slowing the accumulation of hyper‐phosphorylated, insoluble tau filaments. Herein, we report on nonclinical and clinical studies that assessed the effect of LY3372689 on brain OGA enzyme occupancy (EO). Method Brain OGA EO of LY3372689 was measured in the frontal cortex of rats using tracer LSN3291920, a non‐fluorinated analog of a positron emission tomography (PET) radioligand 18F‐ LY3316612. A single oral dose study in healthy volunteers (HV) utilizing18F‐LY3316612 is ongoing to assess brain OGA EO of LY3372689 (NCT03944031). The study consists of up to 5 Cohorts (N = 3 – 6 subjects per Cohort). Upon completion, each subject will have participated in one cohort and have received a baseline PET scan and up to two post‐dose PET scans. In the initial cohorts, the post‐dose PET scans were conducted at approximately 2 and 24 hours after LY3372689 administration. The study design is adaptive to allow adjustment of the LY3372689 dose, timing of PET scans and pharmacokinetic samples, and number of subjects, pending results of prior cohorts. Result In rat studies, LY3372689 demonstrated a dose‐dependent change in OGA EO following a single oral dose with a maximum EO of greater than 90%. In the human PET study, a total of 12 healthy volunteers across 3 dose cohorts (N = 4 HV per cohort) have been enrolled to date. A plasma concentration‐dependent increase in brain OGA EO was observed with EO exceeding 90% at 24 hours following the highest dose of LY3372689 administered. Conclusion Non‐clinical and clinical EO studies demonstrated that occupancy of the OGA enzyme effectively translated from rats to humans after single doses of LY3372689. The human PET data can be used to support LY3372869 dose selection for efficacy trials in tauopathies.